Dearie [compact disc, unabridged] : the remarkable life of Julia Child - Spitz, Bob (Random House Audio, 2012)
A definitive, affectionate biography of one of America's most beloved personalities, Julia Child. This in-depth and intimate narrative is full of fresh information and insight that explores Child's amazing journey in both her personal and professional life.